FFS "Walther Herwig" von erster Forschungsfahrt zurück - Messtorff, J. (1963)
Johann Heinrich von Thunen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung – Information on Fishery research in 2010